P231 The impact of indacaterol (Onbrez®) on the daily lives and health status of patients with COPD: interim results. (14th November 2013) - Jones, PW; Saralaya, D; Morjaria, JB; Quadrino, T; Qurbain, A
Abstract : Introduction: The GOLD guidelines recommend that the COPD Assessment Test (CAT) 1 can be used in guiding and optimising therapy, however there is little evidence on its use in monitoring treatment. Aim We have conducted a 6-month prospective observational study describing the impact of COPD on daily life, following the initiation of maintenance indacaterol, a once-daily long-acting beta-agonist. Method: Subjects from 39 UK GP practices (April 2012 to May 2013) with a diagnosis of COPD and were newly-prescribed indacaterol for routine COPD management, either as maintenance mono-therapy or add-on therapy to long-acting muscarinic antagonists (LAMA) were recruited. Here we present interim results of completed CAT and a descriptive Daily Life Impact Questionnaire (DLIQ), developed for specifically for the study, at treatment initiation and 6–8 weeks. Further assessments will be made at 6 months, when treatment changes in addition to indacaterol will be recorded. Results: One hundred and three subjects (61 males, 42 females), with a mean age of 67 years (range 44–86) and a median baseline FEV1% predicted of 61% (n = 100; IQR 51–70%) were recruited. Median time from diagnosis to indacaterol initiation was 6 months (IQR 0–37). Of the 86 (83.5%) subjects evaluated for change in CAT score, 65 (76%) had a reduction (i.e. improved health status), 18 (21%) increased and 3 (3%) remained the same (Figure 1 ); with a mean overall change of -4.1 (SD ± 5.6; p < 0.001). Fifty-nine (69%) subjects had a ≥2 point (clinically significant) reduction in CAT score. Ninety-two patients completed the DLIQ; 42 (46%) patients reported an improved ability to perform activities important to them, which had previously been rated as being challenging (e.g. walking, gardening, housework). Conclusion: The CAT appears responsive to treatment for COPD with indacaterol when assessed in routine practice and the average size of improvement was large. Alongside this mean improvement, nearly half of patients reported the ability to do more activities that previously they had found difficult. These initial results require further confirmation when full results are available at 6 months. References: 1. Jones PW, Harding G, Berry P, Wiklund I, Chen WH, Kline Leidy N. Development and first validation of the COPD Assessment Test. Eur Respir J 2009;34:648–54